Guidelines for In-service Training Program for Need-based Integration of ICT in Schools - Iqbal, Zafar (JOURNAL OF INDIAN EDUCATION, 2016)
For the purpose of quality education in primary schools, Municipal Corporation of Delhi had initiated ‘Sharda’ Project for Computer Aided Learning Program (CALP). Besides, in order to empower primary teachers of MCD Schools with ICT skills, MCD initiated ‘Shiksha’ project, in collaboration with the Microsoft Corporation (India) Ltd under its program named ‘Partners in Learning’. A 12 days In-Service Training Program on ICT, at its six science centers under the ICT trainers of Microsoft Corporation (India) Ltd (CALP-MCD, 2006) was organized under this programme. Investigator studied the extent of training in ICT, the availability of ICT to the teachers in MCD School. Evaluation of the training in ICT in terms of attainment of competencies conducted a need assessment in further ICT training for the teachers and prepared four phased guidelines for future ICT in-service training for school teachers.